Effects of weaning time, light regime, and stocking density on growth, condition, survival, and cannibalism rates in northern pike (Esox lucius L.) larvae and early juveniles under intensive culture - Imentai, Aiman; Bondarenko, Volodymyr; Pěnka, Tomáš; Policar, Tomáš (Frontiers in Marine Science, 2024)
In this study, three separate experiments were conducted to optimize the intensive larviculture of pike (Esox lucius L.) under different weaning times, light regimes, and stocking densities. In the first experiment, larvae were fed sequential combinations of live feed (LF), co-feeding with dry starter (DS), and only DS feed for 18 days as follows: 9 days LF followed by 3 days co-feeding and 5 days DS (group A); 6 days LF followed by 3 days co-feeding and 9 days DS (group B); 3 days LF followed by 3 days co-feeding and 12 days DS (group C); and DS alone for 18 days (group D). Fish fed LF had significantly higher growth rates than those fed a dry diet (p< 0.05). Extending the feeding period on LF resulted in a significantly higher growth rate (24.6% d−1), variability (13.5%), and heterogeneity (299.5% d−1) than fish fed a DS. In the second experiment, the effect of the light regime was assessed at eight different levels (L0:D24; L24:D0; L16:D8; L4:D4:L4:D4:L4:D4; L8:D4:L8:D4; L12:D12; L8:D16; and L4:D8:L4:D8). The growth and survival of the larvae increased with increasing light period. Groups exposed to complete light (L24:D0) and 16 h of light (L16:D8) exhibited significantly higher weight gain and specific growth rate (SGR, %) than the other groups. The highest survival was observed in fish reared with complete light (68.5 ± 4.5%) and an L8:D4:L8:D4 light regime (61.4 ± 5.2%). All larvae maintained under L0:D24 died during the experiment. The third experiment tested the effect of the fish density within four experimental groups: 10 ind L−1, 20 ind L−1, 40 ind L−1, and 80 ind L−1. Fish at densities of 20 and 40 ind L−1 had significantly higher weight gain and SGR (%) than those in the other groups. The highest survival was in fish reared with 20 ind L−1 density (72.5 ± 8.5%). Fish at densities of 10 and 80 ind L−1 showed significantly higher cannibalism rates than those in the other groups. These results indicated that weaning time, photoperiod, and stocking density play significant roles in early pike larval performance.